Symptom presentation after concussion and pre-existing anxiety among youth athletes - Kent, M.; Brilliant, A.; Erickson, K.; Meehan, W.; Howell, D. (International Journal of Sports Medicine, 2020)
Our purpose was to evaluate the effect of self-reported pre-injury anxiety diagnosis on persistent symptom development, vestibular symptom severity, and balance control among youth who sustained a concussion. We performed a retrospective study of patients seen at a specialty pediatric concussion clinic. Patients were 18 years of age or younger, examined within 10 days of concussion, and received care until full recovery. A questionnaire was used to assess pre-existing medical and psychiatric conditions, including anxiety. Our main outcomes were prolonged symptom recovery defined as persistent symptoms for > 28 days after concussion) and severity of vestibular symptoms. Patients who reported pre-injury anxiety (n=43; median age=14.9 years; 37% female) were more likely to experience symptoms >28 days post-injury (76 vs. 54%; p=0.04) than those without pre-existing anxiety (n=241; median age=14.9 years; 53% female). After adjusting for sex, history of migraine, depression and ADHD, however, there was no independent association between pre-existing anxiety and prolonged symptom duration (adjusted odds ratio=2.34; 95% CI=0.083-6.63; p=0.11). Pre-existing anxiety was independently associated with self-reported nausea/vomiting severity (ß coefficient=0.59, 95% CI=0.07-1.11). A pre-existing anxiety diagnosis does not appear to be associated with persistent symptoms after concussion, although it may be associated with post-injury nausea.